Effect of supplementary irrigation on rice yield in dry land during rainy season. Issue 1 (July 2021) - Anshori, A; Suswatiningsih, T E; l Viandari, N A; Rajiman; Mujiyo
Abstract: Climate change causes change in rainfall patterns, which will affect water availability. Water is a limiting factor for rice production on dry land. Increasing rice yields on dry land requires precise water management. This study aimed to investigate the effect of supplementary irrigation when it does not rain on rice yields in dry land during rainy season. The research was conducted on dry land in Playen, Gunung Kidul, Daerah Istimewa Yogyakarta, Indonesia during rainy season of November 2020 to February 2021. The treatments were supplementary irrigation if 1 day without rain (A1), if 2 days without rain (A2) and if 3 days without rain (A3), and they were compared to control without supplementary irrigation (A0). This research used a randomized completely block design, each treatments replicated 4 times. The results showed A1 gave the highest grain yield, namely 7.786 ton ha −1, significant different with other treatments of A2, A3 and A0. Dry straw of A1 was 7.324 ton ha −1, significant different with A2, A3 and A0. Carbon absorption of A1 was 6.860 ton ha −1, consisting of carbon in grain 3.575 ton ha −1 and straw 3.285 ton ha −1, it was significant different with other treatments of A2, A3 and A0 (p<0.05; n=16). B/C A2 1.73 was highest from the others and its farmers have profit Rp. 19, 276, 360 ha −1 .